2021
DOI: 10.1213/ane.0000000000005796
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Severe Anesthetic-Related Critical Incidents and Risks From the South African Paediatric Surgical Outcomes Study: A 14-Day Prospective, Observational Cohort Study of Pediatric Surgical Patients

Abstract: BACKGROUND: Severe anesthetic-related critical incident (SARCI) monitoring is an essential component of safe, quality anesthetic care. Predominantly retrospective data from low-and middle-income countries (LMICs) report higher incidence but similar types of SARCI compared to high-income countries (HIC). The aim of our study was to describe the baseline incidence of SARCI in a middle-income country (MIC) and to identify associated risk for SARCI. We hypothesized a higher incidence but similar types of SARCI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Hormonal factors; The average age of menarche in girls is 10 -16 years. 13 In this study, it was found that subjects aged ≥10 years (36.4%) were 4 out of 11 girls experiencing cardiovascular complications. In post-pubertal children, hormones in the body, such as estrogen, progesterone, and cortisol, can influence various aspects of the cardiovascular system, nervous system, and inflammatory response, all of which can impact how the body responds to anesthesia.…”
Section: Discussionmentioning
confidence: 66%
“…Hormonal factors; The average age of menarche in girls is 10 -16 years. 13 In this study, it was found that subjects aged ≥10 years (36.4%) were 4 out of 11 girls experiencing cardiovascular complications. In post-pubertal children, hormones in the body, such as estrogen, progesterone, and cortisol, can influence various aspects of the cardiovascular system, nervous system, and inflammatory response, all of which can impact how the body responds to anesthesia.…”
Section: Discussionmentioning
confidence: 66%
“…This is essential if sustainable development goal 3, ensuring healthy lives and promoting well-being for all ages, is to be met and preventable surgical deaths in children ended by 2030. 6 This issue of Anesthesia & Analgesia includes a prospective observational study by Cronjé et al 7 of severe anesthetic-related critical incidents (SARCIs) in 2024 patients at 43 government-funded hospitals, including district, regional, and tertiary referral centers across South Africa. A total of 426 SARCIs were documented in 322 of 2024 (15.9%) patients.…”
Section: Glossarymentioning
confidence: 99%
“…This issue of Anesthesia & Analgesia includes a prospective observational study by Cronjé et al 7 of severe anesthetic-related critical incidents (SARCIs) in 2024 patients at 43 government-funded hospitals, including district, regional, and tertiary referral centers across South Africa. A total of 426 SARCIs were documented in 322 of 2024 (15.9%) patients.…”
mentioning
confidence: 99%